THE INFLUENCE OF MOVIE MAKER IN M-LEARNING MODEL AND LEARNING MOTIVATION TOWARD THE SPEAKING ABILITY OF ELEVENTH GRADE STUDENTS AT STATE SENIOR HIGH SCHOOL 1 PAYUNG - Mika Andika (ELTE Journal (English Languange Teaching and Education), 2020)
This study was to investigate the Influence of Movie Maker in the M-Learning Model and learning motivationtoward the speaking ability of eleventh-gradestudents at State Senior High School 1 Payung. The population of this study is all of the eleventh-grade students of Senior High School 1 Payung, in the academic year of 2019/2020. The sample was 60 students taken by two-stage random sampling. In carrying out the research, the researcher used factorial design. To know the classification of students who had high and low motivation. The researcher was conducted 20 items. Then, in analyzing the data used independent sample t-test and two-way ANOVA. The result of this study indicated that; Firstly,there was asignificant difference in speaking ability between eleventh-grade students with high and those with low motivation who were taught through collaborative learning methods by using Movie Maker.Secondly, there was asignificant difference in speaking ability between eleventh-grade students with high motivation and those with low motivation who were taught by using conventional teaching techniques.Thirdly, there was asignificant difference in speaking ability between eleventh-grade students of high motivation who were taught through collaborative learning methods by using Movie Maker and those who were taught by using conventional teaching techniques.Lastly, there was not any significant interaction effect of the collaborative learning method by using Movie Maker and learning motivation towards students’ speaking ability.